Social Media Sites and the Spread of Suicide Among Their Users - maoucha, abdelhafid (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
the phenomenon of suicide in the Algerian society is one of the anomalies that has seen an unprecedented tangible rise in recent times, prompting us to be alert in order to detect its causes. According to this standpoint, there are apparent and hidden reasons that necessitates us to discover the problems in the Algerian family, that can be directly attributed to the researcher’s view of technological and media liberalization, as well as the extraneous culture that carries along with it values that are forgeign to Algerian families. According to the researcher, social media platforms are among the reasons that has become a legitimate fear and a constant concern for Algerian families due to the sheer number of discussion forums whose visitors are mostly adolescents, whom are more exposed to addiction to social networking sites, which in turn may lead some of them to commit suicide.